2010
DOI: 10.1016/j.ijgo.2010.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening with naked-eye visual inspection in Colombia

Abstract: The use of VIA-VILI simulating colposcopic procedures and provided by nurses represents a good alternative for implementing see-and-treat programs in Latin America. Program constraints should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 19 publications
2
22
1
3
Order By: Relevance
“…The present study reported positive VIA testing in 29.5% of the entire studied population which was higher than that reported in the previous studies (7-12%) (Murillo et al, 2010;Phongsavan et al, 2011;Nessa et al, 2013;Castle et al, 2014). The discrepancy between the rate of positive VIA testing found in our study and the others could be explained by VIA testing performance in different groups of patients.…”
Section: Discussioncontrasting
confidence: 94%
“…The present study reported positive VIA testing in 29.5% of the entire studied population which was higher than that reported in the previous studies (7-12%) (Murillo et al, 2010;Phongsavan et al, 2011;Nessa et al, 2013;Castle et al, 2014). The discrepancy between the rate of positive VIA testing found in our study and the others could be explained by VIA testing performance in different groups of patients.…”
Section: Discussioncontrasting
confidence: 94%
“…The 7% rate of positive VIA tests in the present study is similar to the rates reported for Peru (6.8%) [20] and Colombia (7.4%) [21], but lower than the rates found in Mongolia (12.6%) [22], Kenya (13.2%) [19], Ghana (13.2%) [13], and Thailand (13.3%) [12]. Whether this represents a difference in the prevalence of CIN or is related to the performance of the test cannot be determined without histology.…”
Section: Discussionsupporting
confidence: 90%
“…Cost-effectiveness evaluation of conventional cervical cytology and HPV testing for cervical screening in Colombia have shown that HPV testing every 5 years in women over 30 years of age is a cost-effective strategy, provided that the cost of the HPV test is less than 31 US dollars 29 . In addition, a demonstration project in very low income populations near Bogota has shown that screening using visual inspection with acetic acid (VIA) and Lugol's iodine (VILI) is more sentive but less specific than cytology or VIA alone and provides bases to implement see and treat strategies in very deprived populations 30 . The above results led to the ministry of health of Colombia to approve screening strategies based on scientific evidence and to include the use of the HPV test as primary screening test in the social security system, and to expand the VIA-VILI screening program to 5 other very low-resources areas in Colombia.…”
Section: Etiologymentioning
confidence: 99%